PERSPEKTIF KAREN ARMSTRONG TENTANG ISLAMOFOBIA DI MEDIA BARAT - Rachman, Rio Febriannur (Institut Agama Islam Syarifuddin Lumajang, 2018)
Islamophobia written by Karen Armstrong, John L. Esposito, Imam Abdul Malik Mujahid, et al (published by Mizan in 2018) explains how Islamophobia still afflicts some groups, including Westerners (Americans and Europeans). The causes are the materialization of the phenomenon of terrorism, ISIS, and wahabism which are considered as radical. Such representations are established by the mass media. The definition of Islam in the Western media is closely related to the distortion of meaning, sentiment and stigma. Though, some write objective defense for Islam.